2001
DOI: 10.1063/1.1415447
|View full text |Cite
|
Sign up to set email alerts
|

Vibrational relaxation of the free terminal hydroxyl stretch in methanol oligomers: Indirect pathway to hydrogen bond breaking

Abstract: Vibrational relaxation of methanol-d ͑MeOD͒ in carbon tetrachloride has been investigated via ultrafast infrared pump-probe experiments. Exciting at 2690 cm Ϫ1 , only the free O-D ͑where the D is not H-bonded͒ stretching mode is initially populated. For MeOD mole fractions р0.025, a 2.15 ps single exponential decay is observed. At mole fractions у0.0375, the signal decays ͑2.15 ps decay time͒ below zero ͑increased absorption͒ and then recovers on time scales of 22 ps and ӷ300 ps. The increased absorption indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
75
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(81 citation statements)
references
References 40 publications
6
75
0
Order By: Relevance
“…The intensity of the band at 3350 cm À1 is increased compared to the band at 3480 cm À1 as the concentration of phenol increases. This observation is similar to that for the concentration dependence of methanol in CCl 4 [7,[39][40][41][42].…”
Section: Methodssupporting
confidence: 87%
See 3 more Smart Citations
“…The intensity of the band at 3350 cm À1 is increased compared to the band at 3480 cm À1 as the concentration of phenol increases. This observation is similar to that for the concentration dependence of methanol in CCl 4 [7,[39][40][41][42].…”
Section: Methodssupporting
confidence: 87%
“…Based on the above observations, we proposed that the band at 3350 cm À1 was due to the d-type OH stretching mode, while the band at 3480 cm À1 was the ctype. The b-type OH group, which accepts but does not donate, may have a similar frequency to that of phenol monomer, as shown for methanol oligomers in CCl 4 solution [7,[39][40][41][42].…”
Section: Absorption Spectra Of Phenol Complexesmentioning
confidence: 85%
See 2 more Smart Citations
“…12) It is found that lifetime of the OH stretch depends on the strength of the hydrogen bond; for isolated methanol, the VER times (T 1 ) are in a picosecond order, 13), 14) and it becomes shorter than 1 ps when it forms hydrogen bond. Figure 7 shows IR absorption spectra of the OH and OD stretch region of methanol in isotopically diluted solutions.…”
Section: Oh Stretching Mode Of Methanolmentioning
confidence: 99%